Natural history of carotid artery free-floating thrombus—A single center, consecutive cohort analysis - Müller, Mandy D.; Raptis, Nikolaos; Mordasini, Pasquale; Z'Graggen, Werner; Raabe, Andreas; Schucht, Philippe; Heldner, Mirjam R.; Bervini, David (Frontiers in Neurology, 2022)
Introduction Carotid free-floating thrombus (CFFT) is a rare cause of stroke and is thought to be associated with a high risk of recurrent cerebrovascular ischaemic events. The existing data on the natural history and optimal treatment modalities of CFFT is scanty and no clear recommendations exist. Objective A retrospective analysis of a single-centre cohort of consecutive patients diagnosed with CFFT was conducted, investigating the risk for recurrent cerebrovascular ischaemic events. Methods We performed a single-centre retrospective analysis including all patients presenting at our tertiary centre between January 2005 and December 2020 with symptoms consistent with ischaemic stroke and/or transient ischaemic attack. Digital subtraction angiography (DSA), computed tomography angiography (CTA) or magnetic resonance angiography (MRA) were used to diagnose CFFT. In all included patients, CFFT was confirmed with a second imaging modality. CFFT was defined on imaging as a defect in contrast filling extending into the carotid lumen. We gathered information on vascular risk factors, diagnosis and follow-up methods, modality of treatment and neurological outcome. A survival analysis was performed, assessing the risk for recurrent cerebrovascular events. Results In total, N = 62 patients presenting with symptomatic CFFT were included. Mean age was 68 years, 69% (43/62) of patients were male, 52% (32/62) current or previous smokers, 76% (47/62) suffered from arterial hypertension, 68% (42/62) from dyslipidaemia, and 31% (19/62) from diabetes mellitus. Overall, 71% (44/62) of patients received any kind of intervention (endovascular or surgical carotid thrombo-endartectomy [CEA]) at any time point during follow-up. 16% of patients (10/62) received intervention within 48 hours after diagnosis of CFFT. The survival analysis and Kaplan-Meier model censoring patients at the time of intervention or last follow-up showed that the risk for any recurrent ischaemic stroke was 19.7% within the first 7 days and 27.4% within 3 months after diagnosis. No patients experienced a new ischaemic stroke beyond 11 days after diagnosis of CFTT (n=17). Conclusions The risk of recurrent ischaemic events in patients with CFFT is high, especially in the first week after diagnosis. Prospective studies are needed to further investigate the optimal management of these patients.